Plasma parameters in pig with metal-hydride cathode under different ways of hydrogen supply - Sereda, I.N.; Tseluyko, A.F.; Ryabchikov, D.L.; Babenko, I.V.; Hrechko, Ya.O.; Hetman, V.A. (Вопросы атомной науки и техники, 2015)
In the paper plasma density dynamic on the axis of Penning discharge with metal-hydride cathode in axial electron flow emission regime have been experimentally investigated. The ion-stimulated desorption influence on emissive characteristics of the source were studied. Sufficient plasma density increasing up to n ≈ 10¹⁰ cm⁻³ was established on the discharge axis when metal-hydride cathode was used. Comparable analysis of the plasma density dynamic under different ways of hydrogen supply was carried out.